Students’ Perception of The Implementation of Content and Language Integrated Learning (CLIL) at Senior High School - Amira Muflicha Daraini; Endang Fauziati; Dewi Rochsantiningsih (AL-ISHLAH: Jurnal Pendidikan, 2021)
This research scrutinized the students' perception of Content and Language Integrated Learning (CLIL) in the teaching and learning process. A qualitative approach as a primary framework was employed with a case study method. Twenty students were involved in this research. The information was gathered through questionnaires and interviews. Of the twenty participants, only three participated in the interview session. The results reveal that most students gave tremendous perceptions of CLIL implementation, understanding the teachers’ instructions, being comfortable at some point in the class, and enriching their vocabulary. The findings of the study are envisioned to bring light to other teachers to reflect and develop themselves. Moreover, the study aimed to contribute to the schools’ policy-making, which means undertaking the CLIL program.